DETERMINATION OF THE PROTEINS, LIPIDS AND FATTY ACIDS IN LENTINUS EDODES MYCELIA BIOMASS - Mustafin K.G.; Bisko N.A.; Kalieva A.K; Tapenbayeva I.E. (Academic Journal of Physical and Chemical Sciences, 2020)
Higher Basidiomycete mushrooms are currently of interest because they are a rich source of various bioactive natural products. Lentinus edodes is one of the most promising species of xylotrophic fungi. In this paper crude proteins, lipids and fatty acids in the deep mycelium of L. edodes 2541 have been determined. It was shown that the total protein content in the fungal biomass was 23.0%, and lipids - 7%. Analysis of the fatty acid composition of the deep mycelium of L. edodes 2541 showed that it is dominated by polyunsaturated diene linoleic (C18: 2) acid - 69% of the total fatty acids. Polyunsaturated fatty acids are indispensable components of nutrition, because, like essential amino acids, they cannot be synthesized in the human body. It was demonstrated that in the composition of the lipids of the strain L. edodes 2541 the amount of unsaturated fatty acids (75%) significantly exceeds the amount of saturated fatty acids (24%). In this regard, the degree of lipids unsaturation was 1.46.